2010
DOI: 10.1007/s10533-010-9538-y
|View full text |Cite
|
Sign up to set email alerts
|

Is chloride a conservative ion in forest ecosystems?

Abstract: Chloride (Cl -) has often been assumed to be relatively unreactive in forest ecosystems, and is frequently used as a conservative tracer to calculate fluxes of water and other ions. Recently, however, several studies have detailed cycling of Cl -in vegetation and soils. In this study Cl -budgets are compiled from 32 catchment studies to determine the extent to which Cl -is conserved in the passage through forest ecosystems. Chloride budgets from these sites vary from net retention (input>output) to net release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 50 publications
1
70
0
Order By: Relevance
“…Chloride is widely used as a semi-conservative tracer (Shaw et al, 2008;Jin et al, 2011). We must caution against the uncritical use of chloride as a tracer as it is not conservative (Svensson et al, 2012). This may not be problematic when there are significant chloride inputs, but can lead to inappropriate conclusions when chloride is in short supply.…”
Section: Discussionmentioning
confidence: 99%
“…Chloride is widely used as a semi-conservative tracer (Shaw et al, 2008;Jin et al, 2011). We must caution against the uncritical use of chloride as a tracer as it is not conservative (Svensson et al, 2012). This may not be problematic when there are significant chloride inputs, but can lead to inappropriate conclusions when chloride is in short supply.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of Cl -has often been used as a conservative tracer for the calculation of water fluxes. However, Svensson et al (2012) found that on sites with low Cl -deposition, Cl -may not exhibit conservative behaviour, such as those located far inland away from marine influences. One mechanism suggested is related to vegetation dynamics, with Cl -sequestration resulting from increased biomass growth (Lovett et al 2005).…”
Section: Application Of Mina Trêsmentioning
confidence: 96%
“…Chlorine compounds are highly soluble in water and mobile in soils, so transport of atmospherically derived Cl through terrestrial ecosystems is rapid and conservative if there is active hydrologic flow. Weathering and other internal sources of Cl are generally negligible compared to atmospheric deposition [34], and although some cycling of Cl has been observed in Swedish forest organic horizons [35], the effect of this on the full-profile or catchment input-output budgets appears limited [36]. The calculated water flux was then used to calculate solute fluxes through the soil profile.…”
Section: Water Budgetmentioning
confidence: 99%